Epalrestat-cytosine cocrystal and salt structures: attempt to control E,Z -> Z,Z isomerization - Nangia, Ashwini Kumar; Battini, Swapna (Crystal Growth & Design, 2017)
Cocrystallization of the anti-diabetic drug Eparlestat (EPR) with cytosine (CYT) gave EPR‒‒CYT-H+ form I, a salt-cocrystal hybrid structure, salt hydrate (EPR‒‒CYT-H+‒H2O, 1:2:1), and non-stoichiometric solvates of EPR‒‒CYT-H+ with EtOH/n-PrOH included in the rhombohedral symmetry voids, referred to as form II. Desolvation of EPR‒‒CYT-H+ form II solvates resulted in an unsolvated form II of EPR‒‒CYT-H+ which was characterized by DSC, TGA and NMR. The carboxylate•••cytosinium synthon was observed in the salts structure along with the uncommon CYT-H+•••H+-CYT base pairing in the structures of salt-cocrystal hybrid and salt hydrate. The crystalline forms were characterized by spectroscopic (IR, NMR), thermal (DSC, HSM, TGA), powder X-ray diffraction (PXRD) and single crystal X-ray diffraction (SC-XRD) techniques. The intent of using the salt/ salt-cocrystal forms as a means to stop the E,Z  Z,Z isomerization of EPR was not successful in photo-irradiation experiments.